Consistency of low carbon economy - Godecke, Marcos Vinicius (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708940 This study uses literature review searching to conclude on the consistency of the Low Carbon Economy from the discussion of their basic assumptions about the existence of global warming and its anthropogenic origin, as it is not the object of consensus in the scientific community. The study reunites strong evidence about the phenomenon existence and its consequences, especially in developing countries, characterizing the actions towards the Low Carbon Economy as relevant.